A prosódia na organização discursiva de conversações de sujeitos afásicos - Moura, Chirlene Santos da Cunha (2016)
This research explores the prosodic emphasis as effect of meaning in instances of discourse reorganization of aphasic subjects. It aims at identifying the prosodic resources used by the aphasic subjects in spontaneous conversations, with special attention given to intonation and focuses on analysing emphasis from the point of view of Conversation Analyhsis (Marcuschi, 1986) and of the Interational Theory of Intonation (Brazil, 1985). Spontaneous conversations of four aphasic subjects (one female and three male) that were participants in the Grupo de Convivência de Afásicos at the Catholic University of Pernambuco were collected and analysed. Data of repetition/ recovery of words were selected as relevant material for acoustic investigation of prosodic emphasis on the software PRAAT. The results point to the conclusion that the aphasics organize their conversation with resources and structure captured by the Analysis of Conversation, such as turn taking, repetition/ recovery, hesitation, as well as prosodic elements such as pause, intonation, vowel lengthening, that convey emphasis. From categories considered by the Interational Theory of Intonation, tone units, pauses, prominence and different tones were observed. The PRAAT spectrographic analysis shows that the contrast between repeated and recovered words were different not only with respect to vowel lengthening and syllable duration, but also with respect to peak of F0 and intensity. Those variations attest to the generation of new meanings to the same repeated word. Therefore, the aphasic subjects, who display a general slow rate of speech and whose language is somehow disorganized, and who have difficulty of lexical access, preserve and maximize the prosodic resources at the level of phrase and discourse that have the function of facilitating the conversational flow.